Exposure of Seminiferous Tubules of Immature Rats to Cryoprotective Media of Various Compositions - Volkova, Natalya O.; Yukhta, Mariya S.; Chernyshenko, Lyudmyla G.; Stepanyuk, Lyudmyla V.; Sokol, Larysa V.; Goltsev, Anatoliy M. (Problems of Cryobiology and Cryomedicine, 2017)
The development of new methods aimed at preserving potential fertility before the cytotoxic therapy for individuals of pre-adulthood is an actual area of medical and biological research. The research compares the effect of exposure to media of different composition on morphological parameters and metabolic activity of cells of testicular convoluted tubules of sexually immature rats. Cryopreservation of testicular tissues requires the use of appropriate protocols, ensuring the high viability and functional activity at the background of minimization of damages in transplant material. It has been established that a 30-minute exposure of the tissue samples in media based on Hanks solution and 50 g/l bovine serum albumin supplemented with either 0.6 M DMSO or 0.7 M glycerol did not result in the damage of spermatogenic epithelium and to the decrease in metabolic activity of the cells (MTT test and lactate dehydrogenase activity). Exposure of the testicular convoluted tubules of immature rats during 45 and 60 min in cryoprotective media supplemented with 0.6 M DMSO, 0.7 M glycerol, 50 g/L polyethylene oxide with molecular weight 400 and 0.1 M sucrose led to the manifested desquamation, appearance of acellular areas, reduced density of spermatogenic epithelium cells and their metabolic activity. The findings could be used to substantiate and develop the effective techniques for cryopreservation of seminiferous tubules of immature rats. Probl Cryobiol Cryomed 2017; 27(3): 203–218